AN ANALYSIS OF THE PROCESS CONCERNING THE DUIT PANGUMBANG AUH (PISEK) AND MAMANGGUL IN THE PRELIMINARY PROCESS OF DAYAK NGAJU TRADITIONAL MARRIAGE IN CENTRAL KALIMANTAN - Lorean Andreas Novembri; Suriansyah Murhaini; Putri Fransiska Purnama Pratiwi; Yacob Ferdinan M (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Marriage customs in public Dayak Ngaju in Kalimantan Middle is an important part of the social and cultural life system regulated by customary law Which inherited in a way hereditary. In process going to marriage Customary law has several important stages, including Pangumbang Auh (Pisek) and Mamanggul. Pangumbang Auh is the initial stage of the proposal, marked by the groom's giving of money or objects to the bride's family as a symbol of their seriousness towards marriage. Next, Mamanggul is a traditional deliberation process between the two families to discuss the matter. various agreement related implementation marriage like Determining the timing of marriage and fulfilling customary requirements. This study aims to analyze the process, social meaning, and function of customary law from Pangumbang Auh and Mamanggul in the Dayak Ngaju customary marriage system. The research method used is normative juridical with a qualitative approach through literature study. The results show that these two stages play an important role in building family agreements and maintaining the continuity of customary legal values in the Dayak Ngaju community.